Coronavirus Disease 2019 and Hospital Readmissions: Patient Characteristics and Socioeconomic Factors Associated With Readmissions in an Urban Safety-Net Hospital System. Issue 2 (February 2022) - Gore, Victoria; Li, Zeyu; Drake, Carolyn B.; Heath, Jacqueline L.; Raiszadeh, Farbod; Daniel, Jean; Fagan, Ian
Abstract : Background: It is not yet known whether socioeconomic factors (ie, social determinants of health) are associated with readmission following hospitalization for coronavirus disease 2019 (COVID-19). Methods: We conducted a retrospective cohort study of 6191 adult patients hospitalized with COVID-19 in a large New York City safety-net hospital system between March 1 and June 1, 2020. Associations between 30-day readmission and selected demographic characteristics, socioeconomic factors, prior health care utilization, and relevant features of the index hospitalization were analyzed using a multivariable generalized estimating equation model. Results: The readmission rate was 7.3%, with a median of 7 days between discharge and readmission. The following were risk factors for readmission: age 65 and older [adjusted odds ratio (aOR): 1.32; 95% confidence interval (CI): 1.13–1.55], history of homelessness, (aOR: 2.03 95% CI: 1.49–2.77), baseline coronary artery disease (aOR: 1.68; 95% CI: 1.34–2.10), congestive heart failure (aOR: 1.34; 95% CI: 1.20–1.49), cancer (aOR: 1.68; 95% CI: 1.26–2.24), chronic kidney disease (aOR: 1.74; 95% CI: 1.46–2.07). Patients' sex, race/ethnicity, insurance, and presence of obesity were not associated with increased odds of readmission. A longer length of stay (aOR: 0.98; 95% CI: 0.97–1.00) and use of noninvasive supplemental oxygen (aOR: 0.68; 95% CI: 0.56–0.83) was associated with lower odds of readmission. Upon readmission, 18.4% of patients required intensive care, and 13.7% expired. Conclusion: We have found some factors associated with increased odds of readmission among patients hospitalized with COVID-19. Awareness of these risk factors, including patients' social determinants of health, may ultimately help to reduce readmission rates. Abstract : Supplemental Digital Content is available in the text.